Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: evidence from occupancy data - Hadi, Muhamad Amir; Narayana, Satya; Yahya, Muhammad Syafiq; Jamian, Syari; Lechner, Alex M.; Azhar, Badrul (Elsevier, 2024)
Urban green spaces such as parks, play a vital role in relieving pressure on urban biodiversity. In Southeast Asia, urban park management often prioritises aesthetic appeal over urban biodiversity conservation. Management of wildlife habitat at the stand and landscape scales is necessary to support land-sharing and land-sparing conservation strategies in urban environments. To date, few studies have looked at the occurrence of urban birds in the context of land sharing and sparing strategies. We investigated how resident and migratory birds utilise urban parks based on stand-level habitat characteristics and landscape metrics. We conducted point count surveys at 49 points to estimate site occupancy and detection probability in 40 parks within highly urbanised Klang Valley, Peninsular Malaysia. Out of 90 species recorded, 14 species had more than 50 % site occupancy. The abundance of palm trees, percentage of shrub, and height of ground vegetation and woody trees positively influenced the occupancy of Black-naped Oriole, Javan Myna, House Crow, Oriental Magpie-Robin, and Yellow-vented Bulbul. While the number of woody trees and elevation negatively influenced the occupancy of Asian Glossy Starling, Spotted Dove, Zebra Dove, and Common Myna. Our findings can contribute to the effective management of urban parks, considering both stand and landscape-level characteristics to support urban biodiversity, ultimately benefiting both resident and migratory bird populations. Our research emphasises the significance of implementing both land-sparing and land-sharing strategies in urban park management. By doing so, we can promote greater avian biodiversity, preserve diverse habitats for birds, and establish crucial ecological corridors within urban landscapes.